UV-Reactive Electrospinning of Keratin/4-Vinyl Benzene Boronic Acid-Hydroxyapatite/Poly(vinyl alcohol) Composite Nanofibers - KAHRAMAN, MEMET VEZİR (WILEY, 2017)
Keratins are the major structural fibrous proteins of hair, feathers, wool, and nail. Because keratin is protein based, cheap, and biocompatible, it has found applications from tissue engineering to textile industry. Simultaneous UV-reactive electrospinning technique is used to fabricate nanofiber scaffolds with 4-vinyl benzene boronic acid-hydroxyapatite/ poly(vinyl alcohol) composite containing different amounts of keratin. Human hair as keratin supports the scaffolds for cell culture applications in our study. Our aim was to obtain nanofiber scaffolds which were designed to be nontoxic. The structure and the morphology of electrospun membranes were investigated by scanning electron microscopy and Fourier transform infrared spectroscopy technique. For the cell culture applications, endothelium (ECV 304) and sarcoma osteogenic (SAOS) cells were seeded on the electrospun fibrous scaffolds. Nanofiber scaffolds were found to have an average diameter of 350 +/- 620 nm. These scaffolds provided a medium for cells to grow. (C) 2015 Society of Plastics Engineers